Newton’s Second Law Teaching Strategies—Identifying Opportunities for Educational Innovation - Victor Ricardo Parra-Zeltzer; Jaime Huincahue; Diana Abril (Education Sciences)
Physics teaching faces challenges due to students’ limited understanding of fundamental concepts such as force and motion, as well as the restricted pedagogical strategies often employed by instructors and the limited variety of approaches to physical foundations. This difficulty is aggravated by the perception of physics as distant from everyday life and by the traditional approach focused on solving mathematical problems. Despite the importance of Newton’s second law, many students confuse the relationships between mass, force, and acceleration, which highlights the need to innovate in teaching practices toward active learning trends. To explore the state of teaching Newton’s second law, a systematic review of the literature was conducted using the PRISMA methodology, analyzing twenty-six articles from the Web of Science and Scopus databases. This revealed an increase in interest in teaching this law, especially in 2023. However, the limited number of studies (only 26) also indicates that research on this topic remains scarce and underexplored. Most studies focus on primary and secondary school students (43%) and employ quantitative methodologies (38%). Teaching strategies include problem-solving (40%), simulations (27%), practical activities (14%), and group discussions (12%). Furthermore, it was identified that Newton’s law is primarily represented in scalar form, with limited inclusion of vector approaches, which highlights the need to discuss didactic alternatives that consider both approaches.